Use of sewage sludge in concrete industry - I. L. Chulkova; O. E. Smirnova; A. V. Krasova (Вестник СибАДИ, 2021)
Introduction. The article deals with the actual problem of disposal of industrial waste (sewage sludge). According to the literature data, possible directions of the use of sewage sludge in the production of building materials are identified and considered. Special attention is paid to the proposed variant of systematization of materials, which is based on the dependence of the aggregate state of the sediment on the type of building material. It is proposed to use sewage sludge as a complex additive to improve rheological properties at all stages of heavy concrete hardening.Methods and materials. Studies of the basic properties of raw materials and concrete based on them were determined using standard methods and the requirements of national standards. The material and chemical composition of the sediments, their physical and mechanical characteristics were determined on the basis of the laboratory of the plant of chemical concentrates (Novosibirsk).Results. As a result of the experimental work, the optimal percentage of sewage sludge in the composition of heavy concrete was determined, as well as the ratio of the chemical modifying additive, the optimal composition of concrete was investigated.Conclusion. As a result of the experimental work, the influence of the introduction of sewage sludge modified with plasticizing additives into the concrete composition was established. It has been established that sewage sludge is advisable to use in heavy concrete as a corrective additive without reducing the strength characteristics. In further studies, it is planned to solve the problems of structure formation and study of the interface between the phases of sewage sludge in the composition of concrete; to investigate the relationship between the chemical composition of precipitation and the physical and mechanical properties of a building material.